Understanding fibroblast activation protein (FAP): Substrates, activities, expression and targeting for cancer therapy - Hamson, Elizabeth J.; Keane, Fiona M.; Tholen, Stefan; Schilling, Oliver; Gorrell, Mark D. (Proteomics. Clinical applications, 2014)
Fibroblast activation protein (FAP) is best known for its heightened expression in tumour stroma. This atypical serine protease has both dipeptidyl peptidase and endopeptidase activities, cleaving substrates at a post‐proline bond. FAP expression is difficult to detect in non‐diseased adult organs, but is greatly upregulated in sites of tissue remodelling, which include liver fibrosis, lung fibrosis, atherosclerosis, arthritis, tumours and embryonic tissues. Due to its restricted expression pattern and dual enzymatic activities, FAP is emerging as a unique therapeutic target. However, methods to exploit and target this protease are advancing more rapidly than knowledge of the fundamental biology of FAP. This review highlights this imbalance, emphasising the need to better define the substrate repertoire and expression patterns of FAP to elucidate its role in biological and pathological processes.